Exploring Poly(Ethylene Glycol)-Poly(Trimethylene Carbonate) Nanoparticles as Carriers of Hydrophobic Drugs to Modulate Osteoblastic Activity - Leite, DM (2020)
Current treatment options for bone-related disorders rely on a systemic administration of therapeutic agents that possess low solubility and intracellular bioavailability, as well as a high pharmacokinetic variability, which in turn lead to major off-target side effects. Hence, there is an unmet need of developing drug delivery systems that can improve the clinical efficacy of such therapeutic agents. Nanoparticle delivery systems might serve as promising carriers of hydrophobic molecules. Here, we propose 2 nanoparticle-based delivery systems based on monomethoxy poly(ethylene glycol)-poly(trimethyl carbonate) (mPEG-PTMC) and poly(lactide-co-glycolide) for the intracellular controlled release of a small hydrophobic drug (dexamethasone) to osteoblast cells in vitro. mPEG-PTMC self-assembles into stable nanoparticles in the absence of surfactant and shows a greater entrapment capacity of dexamethasone, while assuring bioactivity in MC3T3-E1 and bone marrow stromal cells cultured under apoptotic and osteogenic conditions, respectively. The mPEG-PTMC nanoparticles represent a potential vector for the intracellular delivery of hydrophobic drugs in the framework of bone-related diseases.